Tobacco retail outlet advertising practices and proximity to schools, parks and public housing affect Synar underage sales violations in Washington, DC. Issue Volume 24:Issue e1(2015) (25th February 2014) - Kirchner, Thomas R; Villanti, Andrea C; Cantrell, Jennifer; Anesetti-Rothermel, Andrew; Ganz, Ollie; Conway, Kevin P; Vallone, Donna M; Abrams, David B
Abstract : Objective: To examine the cross-sectional association between illicit sales of tobacco to minors, Washington DC tobacco outlet advertising practices, retail store type, the demographic make-up of the area surrounding each outlet, and the proximity of each outlet to high schools, recreational parks and public housing. Participants: Seven hundred and fifty tobacco outlets in the DC area, n=347 of which were randomly selected for inspection by the Synar Inspection Program in 2009–2010. Main outcome measures: The presence of tobacco advertisements on the interior and exterior of each outlet, and illicit tobacco sales to Synar Inspection Program youth volunteers. Results: The presence of tobacco advertisements on the exterior of gas stations was much greater than on other retail store types (OR=6.68; 95% CI 4.05 to 11.01), as was the absence of any advertisements at bars or restaurants that sold tobacco (OR=0.33; 95% CI 0.22 to 0.52). Exterior tobacco advertisements were also more likely in predominantly African–American areas of the city (OR=3.11; 95% CI 2.28 to 4.25), and particularly likely on storefronts located closer to parks (OR=1.87; 95% CI 1.06 to 3.28). Illicit sales to minors were more common at gas stations (OR=3.01; 95% CI 1.5 to 6.3), outlets that displayed exterior tobacco advertisements closer to parks (OR=3.36; 95% CI 1.38 to 8.21), and outlets located closer to high schools in majority African–American block groups (OR=1.29; 95% CI 1.07 to 1.58). Conclusions: Findings demonstrate that while illicit tobacco sales to minors are occurring at acceptably low rates by Synar standards, illicit sales vary considerably by retail store type, advertising approach and proximity to high schools, parks and African–American residential areas. Future work may help inform regulatory efforts to reduce youth access at the neighbourhood, city, state and national levels.